2015
DOI: 10.1002/zaac.201500679
|View full text |Cite
|
Sign up to set email alerts
|

Cation Effect on Formation of Preyssler‐type 30‐Tungsto‐5‐phosphate: Enhanced Yield of Na‐encapsulated Derivative and Direct Synthesis of Ca‐ and Bi‐Encapsulated Derivatives

Abstract: The effect of cations in a reaction mixture for the preparation of the Preyssler‐Jeannin‐Pope type 30‐tungsto‐5‐phosphate [P5W30O110Na]14– is investigated. Reaction of phosphate and tungstate with a P/W ratio of ca. 3.9 in an acidic aqueous solution without cations selectively leads to the Dawson‐type 18‐tungsto‐2‐phosphate, [P2W18O62]6–. Amongst all the alkali cations, only Na+ allows formation of the Preyssler‐type polyanion [P5W30O110Na]14–, with an encapsulated Na+ ion, and the product yield can be improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Single-crystal X-ray diffraction (SXRD) analysis showed that the structure of Preyssler-type POM in I agrees with the previous report ( Fig. 1a, Supplementary Data 1 and Supplementary Figure 3) 30 : A bismuth atom (Bi(III)) with a coordination water, which are disordered between two positions, exists on the principal axis of the doughnut-shape POM with pseudo-D 5h symmetry. The Bi(III) is coordinated by five phosphate oxygens (Bi-O = 2.50−2.73 Å).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Single-crystal X-ray diffraction (SXRD) analysis showed that the structure of Preyssler-type POM in I agrees with the previous report ( Fig. 1a, Supplementary Data 1 and Supplementary Figure 3) 30 : A bismuth atom (Bi(III)) with a coordination water, which are disordered between two positions, exists on the principal axis of the doughnut-shape POM with pseudo-D 5h symmetry. The Bi(III) is coordinated by five phosphate oxygens (Bi-O = 2.50−2.73 Å).…”
Section: Resultssupporting
confidence: 90%
“…Here we show that a Preyssler-type [Bi( 30 with a low anion charge facilitates the migration of protons by decreasing the electrostatic interactions between POM and protons. In addition, poly(allylamine) (PAA) is utilized as a polymer because (1) amine groups contribute to increase the number of protonation sites and to extend the hydrogen-bonding network, which results in efficient proton transport and (2) PAA would be positively charged by protonation, and structural stability may improve via electrostatic interaction with POM.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…As {P 5 W 30 } is typically collected by precipitation with KCl, yielding a mixture of K + ‐ and Na + ‐compensated salts (K 14− x Na x [NaP 5 W 30 O 110 ]), we use ion exchange to obtain the acid Preyssler (H 14 [NaP 5 W 30 O 110 ]), which enables systematic variation of the cations present during framework synthesis/crystallization. First, we show that, by varying the amount of K + present, three different Co 2+ ‐bridged structures can be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…As {P 5 W 30 } is typically collected by precipitation with KCl, yielding a mixture of K + -and Na [47] we use ion exchange to obtain the acid Preyssler (H 14 [NaP 5 W 30 O 110 ]), [48] which enables systematic variation of the cations present during framework synthesis/crystallization. First, we show that, by varying the amount of K + present, three different Co 2+ -bridged structures can be synthesized.…”
Section: Introductionmentioning
confidence: 99%